REPLACEMENT OF CORN BRAN IN THE RATION WITH FERMENTED BREAD WASTE FLOUR ON COMMERCIAL PIECES OF MALE BALI DUCK CARCASS (Anas sp) AGE 8 WEEKS - I M. P., Adnyana; Siti, N. W.; Wibawa, A. A. P. P. (Jurnal Peternakan Tropika, 2021)
This study aimed to determine the effect of replacing corn bran in the ration with fermented bread waste flour on commercial pieces of male Bali duck carcass (Anas sp) aged 8 weeks. The research took place at the Laboratory of the Faculty of Animal Husbandry, Udayana University, located at Jalan Raya Sesetan Gang Markisa no 5, Sesetan Village, South Denpasar District, for 8 weeks. The research design used was a completely randomized design (CRD) consisting of 3 treatments and 5 replications and each replication contained 3 ducks with a weight range of 50 ± 2 grams. The three treatments were male bali ducks (Anas sp) which were given complete feed treatment without fermented bread waste (treatment A), male bali ducks (Anas sp) which were given complete feed with fermented bread waste as a substitute for 50% corn bran (treatment B), and male bali ducks (Anas sp) which were treated with complete feed with fermented bread waste as a substitute for 100% corn bran (treatment C). The variables observed were slaughter weight, carcass weight, and percentage of commercial carcass cut. The results showed that the replacement of corn bran in the ration using fermented bread waste flour as much as 50%-100% had a significant effect (P<0.05) on the slaughter weight, carcass weight, and the percentage of commercial carcass pieces on the chest and back while in the commercial carcass of the upper thigh, lower thigh and wing had no significant effect (P>0.05). From the results of this study, it can be concluded that the replacement of corn bran with 50%-100% of waste bread flour can increase the cut weight, carcass weight and commercial pieces of breast carcass. However, it has not been able to increase the percentage of the back, the percentage of the lower thigh, the percentage of the upper thigh and the percentage of the wing.   Keywords: male bali duck (Anas sp), commercial carcass pieces, fermented bread waste flour